PENGARUH DUKUNGAN ORANG TUA TERHADAP PEMELIHARAAN KESEHATAN GIGI DAN MULUT ANAK SDN 4 TENSARAN KABUPATEN ACEH TENGAH - Zakiyah; Nurlaely HS (LLDIKTI WILAYAH XIII, 2025)
The oral health of Indonesian people is still a matter that needs serious attention from health workers. This is seen that 90% of the Indonesian population still suffers from dental and oral diseases. This study aims to determine the effect of parental support on maintaining the oral and dental health of children at SDN 4 Tensaran, Central Aceh Regency. This type of research is analytical with a cross-sectional design. The population in this study were all students of SDN 4 Tensaran, Central Aceh Regency, totaling 234 students. In this study, the sample size obtained was 70 samples from 234 populations at SDN 4 Tensaran, Central Aceh Regency using the Slovin formula. The results of this study indicate that of the 70 respondents, the majority of respondents were not good at maintaining oral and dental health, as many as 42 respondents (60%). And in terms of family support, the majority of respondents received parental support, as many as 42 respondents (60%). Based on the results of the Chi Square statistical test at a 95% confidence level, a P Value of 0.002 (P ≤ 0.05) was obtained. This statistically demonstrates a significant relationship between family support and maintaining children's dental and oral health. Parents are advised to pay closer attention to their children's dental and oral health. Keywords: Dental and Oral Health, Family Support